Business plan: Madeira Heritage Boutique Hotel - Olim, Rui Manuel de (2021)
The reasons people travel has changed over time and have certainly been impacted by the Covid-19 Pandemic, with the urge of unique experiences being each time more noted. Aligned with these motivations, boutique accommodation units have emerged, mainly in the form of hotels. Boutique accommodation is meant to be unique, and customer centred and mostly associated to luxury, for the quality and diversity of the services offered, the conditions and provided and availability to fulfil any requests from guests. This project’s objective is to conceptualize, design and evaluate the economic and financial viability of the creation of a Boutique Hotel like accommodation unit in Porto Moniz, Madeira Island. This unit has a particularly interesting approach since it proposes to have the main offering found in Boutique Hotels but in order to leverage a legal opening will not classify as so. To this end, a business plan was drawn up given its aggregating value for Project valuation. In a first stage, literature review was conducted regarding the definition of tourism and tourist, experience marketing related to tourism, tourism products and trends and finally the types of accommodations, focusing on defining Boutique Accommodation. In the second phase, and in order to respond to the research problem, the usual structure of a business plan was followed: market analysis, internal analysis, competitive analysis, development strategy, objectives and implantation policies, finalizing with the projects economic and financial analysis and conclusions.